The Influence Of Third Party Funds (Dpk), Cost Of Funds (Cof), And Liquidity On Profitability In Indonesian Islamic Banks (BSI) In 2021 - 2024 - Yumna, Talitha Dwi; Alvin Yahya (UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Third party funds are a source of funds for the bank in channeling it back to the community in the form of loans or financing, third party funds collected by the bank will return to the community with a difference in the ratio / profit sharing and / or margin in accordance with the agreed agreement, giving rise to Cost of Fund for the bank against these third party funds. Apart from that, the third party funds can be taken at any time by the customer in accordance with the deposit product so that the bank is obliged to maintain and guarantee financial liquidity both in the long, medium and short term. Bank as an industry also focuses on profitability so that one of its goals is to generate profits or profits. In this research process, researchers carry out a balance sheet study focus to see the level of value of each variable including third party funds, cost of funds and liquidity. The mechanism used regarding this research uses samples from the financial statements of Bank Syariah Indonesia with financial reports presented monthly from 2021-2024. The analysis test is used to be able to see how much influence on each variable by using descriptive testing, classical assumptions, and multiple linear regression. The results of the tests that have been carried out present data that Third Party Funds (DPK), Cost Of Fund (COF), have positive significant results on Profitability. While the results of the liquidity variable proxied by the current ratio are not positively significant to profitability at Bank Syariah Indonesia (BSI) with the period 2021-2024.